Schaum 's outlines of theory and problems of computer graphics - Zhigang, Xiang (McGraw Hill, 2002)
Scores of examples and problems allow students to hone their skills. Clear explanations of fundamental tasks facilitate students' understanding of important concepts. New! Chapters on shading models, shadow, and texture'including the Phong illumination model'explain the latest techniques and tools for achieving photorealism in computer graphics.